Variation of Social Acceptance: Kashimbila Multipurpose Dam Stakeholders in Focus - Wunubo, Bala; Ibrahim, Muhammad Bello (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2019)
Long ago, rivers have always been sustaining livelihoods through the utilization of different natural resources available in their basins. All over the world, many rivers have been dammed in the spirit of performing various purposes: agricultural irrigation, domestic water supply and power generation or flood control. The World Commission on Dams brought into focus the debate on dam related impacts on local economies, societal cultures, livelihoods security and environmental conservation. The outcome of the World Commission on Dams consultation strongly recommended the involvement of stakeholder groups to address appropriately all issues associated with dams. Therefore, the aim of this study is to examine the variation of social acceptance among different project stakeholders. Mixed research method was adopted for the study and the instruments used for data collection were questionnaire, interview and observation. The respondents were drawn from people living within close fringes of the dam. The estimated population of the area is 247, 657 and the sample size of the research is 269. The participants for interview were identified using a stratified sampling method while those whom questionnaire were administered on were identified using simple random sampling. The responses received suggest that dam project capture attention of dam stakeholder groups, if its components are of interest to the community members. These results indicated that there is an existence of variation among Kashimbila Multipurpose Dam (KMD) stakeholder groups in choosing factors that influenced their acceptance. On this basis it is recommended that project developers should always bear in mind the pressing needs of the affected communities during decision and planning processes of the proposed projects.